2007
DOI: 10.1063/1.2715128
|View full text |Cite
|
Sign up to set email alerts
|

Defect distribution in a-plane GaN on Al2O3

Abstract: The authors studied the structural and point defect distributions of hydride vapor phase epitaxial GaN film grown in the [11−20] a direction on (1−102) r-plane sapphire with metal-organic vapor phase deposited a-GaN template using transmission electron microscopy, secondary ion mass spectrometry, and positron annihilation spectroscopy. Grown-in extended and point defects show constant behavior as a function of thickness, contrary to the strong nonuniform defect distribution observed in GaN grown along the [000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
34
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 18 publications
7
34
0
Order By: Relevance
“…IV.G covers the cation-anion vacancy clusters found in InN and InGaN alloys. A wide variety of studies of Ga-vacancy defects generated during epitaxial growth by MBE and metal-organic vapor phase deposition (MOCVD) have shown that similar effects related to growth temperature and stoichiometry can be found as in the traditional compounds, but in GaN oxygen impurities play a decisive role (Rummukainen et al, 2004;Hautakangas et al, 2006;Tuomisto, Paskova et al, 2007), and possibly also hydrogen (Hautakangas et al, 2006;Nykänen et al, 2012).…”
Section: Novel Semiconductors: Iii-n Sic and Znomentioning
confidence: 99%
See 1 more Smart Citation
“…IV.G covers the cation-anion vacancy clusters found in InN and InGaN alloys. A wide variety of studies of Ga-vacancy defects generated during epitaxial growth by MBE and metal-organic vapor phase deposition (MOCVD) have shown that similar effects related to growth temperature and stoichiometry can be found as in the traditional compounds, but in GaN oxygen impurities play a decisive role (Rummukainen et al, 2004;Hautakangas et al, 2006;Tuomisto, Paskova et al, 2007), and possibly also hydrogen (Hautakangas et al, 2006;Nykänen et al, 2012).…”
Section: Novel Semiconductors: Iii-n Sic and Znomentioning
confidence: 99%
“…Indeed the polarity of the growth surface strongly affects the Ga-vacancy defect formation and impurity incorporation in GaN (Rummukainen et al, 2004;Tuomisto, Saarinen, Lucznik et al, 2005;Tuomisto, Paskova et al, 2007). Some evidence of N vacancies with positrons has been found in irradiated (Tuomisto, Ranki et al, 2007) and Mg-doped GaN samples , but further studies are clearly required.…”
Section: Novel Semiconductors: Iii-n Sic and Znomentioning
confidence: 99%
“…Differences in the distribution of acceptor type vacancies near the interface with the substrate have been observed in films of ZnO 26 and GaN 27 depending on the growth polarity and the lattice mismatch. In the samples with a buffer layer, the strain is absorbed near the interface with the substrate and the defects do not propagate into the ZnCdO layer.…”
Section: à3mentioning
confidence: 99%
“…In fact, in GaN high densities of basal plane stacking faults and high V Ga concentrations have been observed to go hand in hand. 14 Furthermore, as in earlier work, a link between the In vacancies and carrier mobility has been suggested, 7 we show the relation of carrier mobility and In vacancy concentration in the samples where the electrical characteristics were measured in Fig. 2.…”
mentioning
confidence: 90%
“…The V Ga concentrations in GaN samples with low dislocation densities are of the same order of magnitude that could be expected from the growth temperature and the calculated formation energies, given that the mobile vacancies are stabilized by impurities ͑such as O in GaN͒ or other defects relatively close to the growth temperature. 14,19,20 As the V Ga and V In concentrations are similar in samples in near-stoichiometric conditions, the formation of the In vacancies must be dictated by other factors than the thermal formation ͑and subsequent stabilization by, e.g., impurities͒ of an isolated In vacancy in an otherwise perfect lattice. On the other hand, assuming that the observed In vacancies were formed directly next to impurities or dislocations leads to an experimentally estimated formation energy of at most 0.7-0.9 eV.…”
mentioning
confidence: 99%